The use of the national system of documentation on the line) SNDL( by PhD students of the third phase - A field study at the Faculty of Humanities and Social Sciences University of M’sila - bounif, Mohamedamine; lamine, Nassira (Journal of Social Sciences and Humanities, 2021)
The current research aims to study the use of the National System for Online Documentation SNDL by PhD students of the third phase, and the two researchers applied their field study to the students of the third phase PhD LMD at the Faculty of Humanities and Social Sciences at the University of M'sila. The researchers found in their results that studentsof the third phase tend to generalize the completion of their academic research from the electronic information sources included in the databases of the national system for online documentation.